The impact of pandemic measures on the behaviour of science students - Ivan Iľko; Viera Peterková (Paidagogos - Society For Philosophy, Theory and Praxis of Education, 2024)
The COVID-19 pandemic has affected the lives and daily routines of people almost everywhere on the planet. Suddenly, working or studying remotely became common for millions of people. In this context, we examine how the daily activities of students in natural science subjects in the field of sports, sleep, work, leisure, eating, and hygiene changed in the context of Slovak Republic. Based on a sample responses collected through an ethogram in April 2021 and subsequently in April 2022, we found through statistical analysis that the behavior of students changed significantly during the pandemic in the area of sleep (p= 0.038). We also found that the behavior of students was not statistically significantly different in the areas of sports, work, leisure, eating, and hygiene. These findings provide a basic characterization of the behavior of students in natural science subjects at a university in Slovak Republic. In the event of another lockdown and deteriorating of epidemiological situation, these findings can provide support to students as well as university educators.